2020
DOI: 10.1103/physrevd.101.024042
|View full text |Cite
|
Sign up to set email alerts
|

Canonical analysis ofn-dimensional Palatini action without second-class constraints

Abstract: We carry out the canonical analysis of the n-dimensional Palatini action with or without a cosmological constant (n ≥ 3) introducing neither second-class constraints nor resorting to any gauge fixing. This is accomplished by providing an expression for the spatial components of the connection that allows us to isolate the nondynamical variables present among them, which can later be eliminated from the action by using their own equation of motion. As a result, we obtain the description of the phase space of ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…As such, we shall study a manifestly first-order formulation of gravity based on N ¼ dðd þ 1Þ 2 =2 number of a priori independent degrees of freedom. Even though alternative manifestly first-order formulations do exist, such as the tetradic-Palatini action (for example, see [38] and its recent canonical study [39]), inconvenient subtleties to our aims arise in those frameworks due to their geometric construction. For instance, unlike the metric, vielbeine are not required to be invertible.…”
Section: A Comprehensive Constraint Analysis Of Palatini Theoriesmentioning
confidence: 99%
“…As such, we shall study a manifestly first-order formulation of gravity based on N ¼ dðd þ 1Þ 2 =2 number of a priori independent degrees of freedom. Even though alternative manifestly first-order formulations do exist, such as the tetradic-Palatini action (for example, see [38] and its recent canonical study [39]), inconvenient subtleties to our aims arise in those frameworks due to their geometric construction. For instance, unlike the metric, vielbeine are not required to be invertible.…”
Section: A Comprehensive Constraint Analysis Of Palatini Theoriesmentioning
confidence: 99%
“…iii) We have shown that the BF -type action principles ( 2) and (32) have the same Hamiltonian formulation (involving only first-class constraints) that the n-dimensional Palatini action has [14,13]. This needs to be so, and not otherwise, because all three actions describe Einstein's general relativity.…”
Section: Second Action Principlementioning
confidence: 87%
“…Substituting them into the action (33) leads to the same intermediate action (10), which following again the approach of Ref. [13] produces the canonical formulation embodied in (26) and thus to the Hamiltonian formulation (30).…”
Section: Second Action Principlementioning
confidence: 95%
See 2 more Smart Citations